FEATURES OF THE PHYSICS TEACHING PROCES - Sultonov Ravshanbek Rustamovich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article aims to provide methodological assistance to students in  teaching  and  learning  physics  in  secondary  schools  based  on  a  psychological approach and science based on the laws of nature.